PENGARUH RIWAYAT KETURUNAN DISMIONREA TERHADAP DISMINOREA PADA REMAJA DI KOTA PEKANBARU - Siti Qomariah; Sara Herlina; Wiwi Sartika (JURNAL KESEHATAN INDRA HUSADA, 2022)
Menstruation is a natural process experienced by normal women which is characterized by bleeding and comes repeatedly every month from puberty to menopause, except during pregnancy. In the menstrual phase, often a woman will feel a problem. The most common problem experienced is dysmenorrhea. Objective: To determine the effect of hereditary history of dysmenorrhea on dysmenorrhea. Method: analytic quantitative research with cross sectional design where all variables were observed at one time. This research was conducted in Pekanbaru City. The sample in this study were young women as many as 60 people. The sampling technique is using Random Sampling where the sample is taken randomly as a respondent. Data processing procedures with Editing, Coding, Processing, Cleaning. Data analysis was univariate and bivariate with chi-square test. The results: univariate results showed that the majority of respondents did not have a family with dysmenorrhea as many as 37 people (61.66%), the majority of respondents did not experience dysmenorrhea as many as 32 people (53.3 %), bivariate results, the majority of respondents had a history of dysmenorrhea and experienced dysmenorrhea as many as 17 people (73.6%) while respondents who did not have a history of dysmenorrhea, the majority did not experience dysmenorrhea as many as 26 (70.3%). Based on the chi-square test, the P Value of 0.000 <0.05 means that there is an influence between the history of dysmenorrhea and dysmenorrhea in adolescents in Pekanbaru City. The result of OR 6.6 means that respondents who have a history of heredity are at risk of experiencing dysmenorrhea 6 times compared to respondents who do not have dysmenorrhea. Conclusion: There is an effect of hereditary history of dysmenorrhea on dysmenorrhea in adolescents in Pekanbaru with a P value of 0.001.